Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.20944/preprints201809.0490.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-Aging Efficacy of Melatonin-Based Cream: Clinical and Instrumental Skin Evaluation

Abstract: Background: Melatonin is a potent mitochondrial, cytoprotective and antioxidant molecule with potentially strong anti-aging properties. Topical melatonin has shown to improve the clinical signs of skin aging. Melatosphere™ is a new lipid-based delivery system able to improve stability and skin penetration of melatonin when used in topical formulations. No clinical studies, using objective instrumental data, are available so far regarding the positive effect of Melatosphere™ in improving wrinkles in women with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In addition, the melatonin main biologically active metabolite, AFMK can stimulate differentiation in human epidermis and promote epidermal barrier formation [34]. Milani et al also found melatonin and its metabolites act as free radical scavengers could improve signs of skin aging evaluated clinically [35]. Thus, we inferred G→B not only increased the melatonin concentration but also lead to the accumulation of melatonin metabolites in plasma.…”
Section: Effects Of Melatonin On a Combination Of Monochromatic Lightmentioning
confidence: 64%
“…In addition, the melatonin main biologically active metabolite, AFMK can stimulate differentiation in human epidermis and promote epidermal barrier formation [34]. Milani et al also found melatonin and its metabolites act as free radical scavengers could improve signs of skin aging evaluated clinically [35]. Thus, we inferred G→B not only increased the melatonin concentration but also lead to the accumulation of melatonin metabolites in plasma.…”
Section: Effects Of Melatonin On a Combination Of Monochromatic Lightmentioning
confidence: 64%
“…[16][17][18] The three studies were recently published between 2018 and 2017. [16][17][18] The aim of the three studies were checked, two studies investigated the effect of anti-aging products on the skin, one study investigated the effect of using melatospherebased cream for two months on skin texture and the other study evaluated the efficacy of topical products including night and day facial creams, night and day lip creams and eye creams to reduce the appearance of wrinkles and transepidermal water loss and to increase skin moisturization. 16,17 The last study investigated the efficacy of different types of anti-aging products but relied on data obtained from self-assessment of customers.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] The aim of the three studies were checked, two studies investigated the effect of anti-aging products on the skin, one study investigated the effect of using melatospherebased cream for two months on skin texture and the other study evaluated the efficacy of topical products including night and day facial creams, night and day lip creams and eye creams to reduce the appearance of wrinkles and transepidermal water loss and to increase skin moisturization. 16,17 The last study investigated the efficacy of different types of anti-aging products but relied on data obtained from self-assessment of customers. 18 There were two trials included, each of the three studies was of a different study design, one of the trials was an open, prospective evaluator-blinded trial, the other trial was controlled clinical and the third study was a prospective cross-sectional study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations